Assessment of genetic diversity of 50 Vietnamese soybean cultivars with different response to ruts by SSR markers - Tra, Vu Thanh; Mau, Chu Hoang; Phuong Lien, Tran Thi (Academia Journal of Biology, 2012)
Simple Sequence Repeat (SSR) are the markers of high polymorphism and stability, which are widely used and effective in studying the genetic diversity of plants. In this paper we present results on the use of 15 SSR primer pairs to analyze the genetic diversity of 50 soybean cultivars having different responses to rust. 14 primer pairs showed polymorphisms. There were 81 alleles have been amplified, amplified alleles of each SSR primer pairs ranged from 4 to 8. Polymorphic information contents of used primers ranged from 0.473 (Satt042) to 0.798 (Satt175). Among 15 SSR primer pairs, 10 have high Polymorphic information content (PIC ³ 0.7). The soybean cultivars were grouped into two groups: Group I included, maily soybean cultivars that are susceptible to rust, group II consisted mostly rust-resistant cultivars. Genetic distance between the two groups is 29%. This information could be used as the basis for selection of soybean cultivars resistant to rust for soybean production, as well as the basis for the selection of soybean varieties with different genetic background for soybean breeding.